Termination Of Employment Relationship Based On Law Regulation Number 11 Of 2020 Concerning Employment Creation - Syahrul Qiram; Faisal Santiago (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The study aims to examine/analyze legal protection for workers/laborers for termination of employment (PHK) due to Force Majeure experienced by the company. The research method used in this proceeding uses normative juridical research methods, namely research that is focused on examining the application of norms or norms in normative law, namely an approach that uses the positivist conception of legis. This concept views law as identical to written norms made and promulgated by authorized institutions or officials. The conception views law as a normative system that is independent, closed, and detached from the real life of society. Based on the research results about Termination of Employment (PHK) due to Force Majuere from the Covid-19 Virus pandemic, many private companies have used it so many have terminated their work relationships so that workers/laborers lose their daily livelihood for themselves and their families. The need for legal protection for the rights of workers/ laborers affected by layoffs is clarified to provide legal certainty. So that there will be no more Termination of Employment experienced by workers/laborers, and also employers take the opportunity to cheat in this situation.